Magnetic diatomite microcapsule corrosion inhibition filler as well as preparation method and application thereof
By aligning the corrosion-inhibiting fillers in the coating, combining epoxy resin and magnetic nanoparticles, the problems of short life and poor barrier properties of existing anticorrosion coatings are solved, and efficient coating barriers and activeness are achieved Anti-corrosion effect extends the service life of the equipment.
Patent Information
- Application Number
- CN202411466077.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2024-12-27
AI Technical Summary
When used on the surface of heavy anticorrosion equipment, the existing anticorrosion coating has a short life and poor barrier properties. The agglomeration and disorderly dispersion of microcapsule fillers lead to increased coating defects and accelerated invasion of corrosive media.
By designing a magnetically active filler with high efficiency loading corrosion inhibitors, the diatomaceous earth microcapsules are arranged in a directional manner in the coating, and combined with epoxy resin, a diatomaceous earth microcapsules corrosion inhibitor filler with magnetic and directional arrangement effects is prepared. , slowly release corrosion inhibitor with LDHs to achieve active corrosion prevention.
It significantly improves the barrier properties and protection capabilities of the coating, reduces coating defects, extends the service life of the equipment, and quickly releases the corrosion inhibitor to form a dense passivation film when corrosive media invades, delaying metal corrosion.
Smart Images

Figure CN119192891A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of anti-corrosion coatings, and in particular relates to a magnetic diatomite microcapsule corrosion-inhibiting filler and a preparation method and application thereof. Background Art
[0002] In the past few decades, organic coatings have become one of the most sensible strategies to delay metal corrosion due to their convenience and low cost. However, the micropores left by solvent evaporation during the curing process of organic polymer coatings are a disadvantage that is difficult to overcome in the coating preparation process. At present, many researchers have reduced the micropores inside the coating by adding fillers and active substances, and the protective performance of the coating has been significantly improved. It is worth noting that due to the excellent loading capacity and functional characteristics of microcapsules, microcapsules have become one of the most effective fillers to improve the barrier properties of coatings and extend the life of coatings. However, the agglomeration and disordered dispersion of microcapsule fillers not only seriously weaken their functional properties and positive effects, but also may affect the cross-linking of the resin matrix, increase the defects of the coating, and thus accelerate the degradation of the coating and the invasion of corrosive media. Therefore, it is necessary to achieve uniform dispersion and directional distribution of microcapsule fillers in resin coatings by improving process methods and preparation strategies.
[0003] Many researchers have done a lot of work on the uniform dispersion of microcapsules in organic resins. For example, Amir H. Navarchian and his colleagues used hexamethylenediamine (HDMA) to modify the surface of polymethyl methacrylate (PMMA) microcapsules. Due to the high interfacial adhesion between HMDA on the surface of the microcapsules and the epoxy resin matrix, the self-healing ability of the modified microcapsules and the protective ability of the composite coating were improved. In addition, Wu et al. studied the effect of graphene oxide (GO) modified microcapsules in steel-based self-healing epoxy anti-corrosion coatings. Infrared spectroscopy, X-ray photoelectron spectroscopy, atomic force microscopy and Raman spectroscopy proved the success of GO modification of microcapsules. Electrochemical impedance spectroscopy tests showed that the impedance modulus of the composite coating with GO modified microcapsules was 3 orders of magnitude higher than that of the blank sample. In addition, Li et al. successfully coated polyaniline on the surface of sodium alginate microcapsules. Tests showed that the hydrophobicity, thermal stability, tensile strength and adhesion to carbon steel of the coating were significantly improved. The test results after the coating was immersed in the corrosive medium for 50 days proved the excellent anti-corrosion efficiency of the coating (99.9943%). At the same time, some researchers have innovated the coating preparation technology and achieved uniform directional distribution of two-dimensional materials in the coating. For example, in order to improve the barrier properties of epoxy coatings, Zhao et al. used electrophoretic deposition technology to transform the random distribution pattern of boron nitride nanosheets into ordered dispersion and orientation, thereby preparing boron nitride-epoxy self-oriented composite coatings. Electrochemical monitoring shows that the impedance modulus of the oriented composite coating is 4 and 2 orders of magnitude higher than that of the blank and randomly dispersed coatings, respectively. Similarly, Fan et al. used a similar method to protonate Ti3C2Tx(f+ -Ti3C2Tx) flakes are oriented and distributed in the epoxy resin coating. Tests show that 1% f + -The epoxy coating of Ti3C2Tx has a nearly perfect internal arrangement structure. In addition, the water absorption rate decreased by 85.33% after long-term exposure to saline solution, and the lowest frequency impedance was improved by 4 orders of magnitude compared with the randomly arranged Ti3C2Tx mixed epoxy coating. In addition, Wang Xiao's team designed a spin coating method to prepare a highly oriented graphene / epoxy (OG / EP) coating with long-term corrosion resistance. Surprisingly, after the OG / EP coating was immersed in a coupled environment of 3MPa pure oxygen and 3.5wt% NaCl for 7 days, the impedance of 0.01Hz still remained at a relatively high level, which was 10 higher than that of pure epoxy (Spin-EP and Spray-EP) and randomly arranged graphite / epoxy coatings, respectively. 3 and 8×10 5 times. The protective mechanism of OG / EP coating is explained as the orientation of graphene, which maximizes the barrier effect of graphene and avoids the formation of graphene conductive network. The above studies have proved that the regular distribution of fillers in the coating is an important strategy to exert the ultimate barrier performance of the coating. However, it is still an unprecedented and challenging task to give microcapsules directional arrangement behavior to improve the comprehensive performance of the coating.
[0004] In order to solve the above problems, the present invention is proposed. Summary of the invention
[0005] From the background technology, we can see that long-lasting heavy-duty anti-corrosion coatings and functional materials that extend the service life of ships and equipment have always been a hot topic of research, reducing equipment corrosion and improving resource utilization efficiency. At present, traditional anti-corrosion coatings such as water-based acrylic acid, polyurea, polyurethane and hydrophobic anti-corrosion coatings prepared from fluorocarbon resins are often used for equipment corrosion protection. Although they achieve excellent anti-corrosion effects in the short term, their short lifespan and poor barrier properties greatly limit the application of the above coatings on the surface of heavy-duty anti-corrosion equipment. Therefore, it is crucial to prepare a coating that can reduce coating defects, increase the barrier capacity of the coating, and at the same time give the coating an active anti-corrosion effect.
[0006] In order to further increase the barrier effect of diatomite microcapsules and improve the barrier properties of the coating to improve the corrosion resistance of the coating, this application further adjusts the distribution state of diatomite microcapsules in the coating on the basis of previous studies, and designs an active anti-corrosion filler that efficiently loads corrosion inhibitors and is oriented in the coating. In this experiment, the ambient pressure was -0.06MPa by reduced pressure impregnation. The corrosion inhibitor was transferred to the inside of the bio-template (diatomite), and LDHs and Fe3O4 were grown on the surface of the bio-template in sequence by hydrothermal synthesis, thereby preparing a magnetic active filler (Fe3O4 / LDHs / DE / corrosion inhibitor), and the magnetic active filler was combined with epoxy resin to prepare an active anti-corrosion coating. Interestingly, under the action of the magnetic field, the active filler will be evenly distributed in the resin matrix in a parallel arrangement to the steel substrate, and the barrier properties of the coating are significantly improved. Moreover, a large amount of corrosion inhibitor stored in the bio-template is slowly released by LDHs, thereby achieving the purpose of active anti-corrosion.
[0007] In summary, in order to achieve the directional arrangement of diatomite microcapsules in the coating and the active corrosion protection of loaded corrosion inhibitors, the present invention uses diatomite as a bridge, assembles LDH with ion adsorption characteristics and corrosion inhibitors, and prepares a diatomite microcapsule with corrosive ions (Cl - ) Diatomaceous earth microcapsule corrosion inhibition filler with adsorption and corrosion inhibition effect. In order to achieve the parallel arrangement of diatomaceous earth microcapsule corrosion inhibition filler in the coating, the diatomaceous earth microcapsule corrosion inhibition filler was modified by using technical means, and the diatomaceous earth microcapsule corrosion inhibition filler with magnetic and directional arrangement effect was prepared.
[0008] In a first aspect, the present application provides a magnetic diatomite microcapsule corrosion-inhibiting filler, wherein the magnetic diatomite microcapsule corrosion-inhibiting filler is a diatomite microcapsule modified with a double metal hydroxide loaded with a corrosion inhibitor, and the diatomite microcapsule is loaded with magnetic nanoparticles;
[0009] The magnetic nanoparticles are Fe3O4 magnetic nanoparticles.
[0010] Preferably, the magnetic diatomite microcapsule corrosion-inhibiting filler is disc-shaped and has a particle size of 10 to 25 μm.
[0011] The second aspect of the present application provides a method for preparing the magnetic diatomite microcapsule corrosion-inhibiting filler according to the first aspect, the preparation method comprising the following steps:
[0012] A mixed solution of sodium acetate, trivalent iron salt and ethylene glycol is prepared, and diatomaceous earth microcapsules modified with double metal hydroxide loaded with corrosion inhibitor are dispersed in the mixed solution, and reacted at 180-200° C. for 12 hours to obtain magnetic diatomaceous earth microcapsule corrosion inhibition filler;
[0013] Among them, the mass fraction of sodium acetate in the mixed solution is 20-30wt%, the ratio of the added amount of trivalent iron salt to sodium acetate is 1:(6-10), the mass ratio of the added amount of double metal hydroxide modified diatomaceous earth microcapsules loaded with corrosion inhibitor to the trivalent iron salt is (1-2):1, and the mass ratio of the amount of ethylene glycol to the trivalent iron salt is (50-75):1.
[0014] Preferably, the preparation method of the double metal hydroxide-modified diatomite microcapsules loaded with corrosion inhibitor is as follows:
[0015] (1) Preparation of double metal hydroxide modified diatomite microcapsules:
[0016] Dispersing diatomaceous earth in water to prepare a diatomaceous earth dispersion containing 0.1 to 0.2 g of diatomaceous earth per 100 g of water, adding a water-soluble nickel salt, a water-soluble cobalt salt, urea and ammonium fluoride to the dispersion, and then reacting at 80 to 140° C. for 8 to 14 hours, and cooling the reaction to room temperature to obtain a solid that is a double metal hydroxide-modified diatomaceous earth microcapsule;
[0017] Among them, Ni 2+ / Co 2+ The molar ratio of is 4 to 2, the total molar ratio of metal cation to urea and ammonium fluoride is: 1: (10 to 20): 8 to 12; the molar mass ratio of metal cation to water is 1 mmol: 60 g;
[0018] (2) Loading corrosion inhibitor sodium phosphate:
[0019] The double metal hydroxide modified diatomite microcapsules obtained in step (1) are mixed with a sodium phosphate aqueous solution, wherein the mass fraction of sodium phosphate in the sodium phosphate aqueous solution is 15-20wt%, 0.5-1g of the double metal hydroxide modified diatomite microcapsules are mixed with 3g of the sodium phosphate solution, and then the mixture is transferred to a vacuum drying oven at 60-80°C until it is completely dried to obtain double metal hydroxide modified diatomite microcapsules loaded with corrosion inhibitor.
[0020] The third aspect of the present application provides the use of the magnetic diatomaceous earth microcapsule corrosion-inhibiting filler described in the first aspect for being arranged parallel to the magnetic substrate in a coating and for corrosion protection.
[0021] Preferably, the magnetic substrate is selected from a steel substrate or a nickel-cobalt alloy substrate.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] 1. The magnetic anticorrosive diatomite microcapsule filler assembled by various technical means in the present invention not only reduces the agglomeration of diatomite microcapsules in the coating compared with the original diatomite and other sheet materials, but also enables the diatomite microcapsules to be arranged in parallel in the coating, thereby significantly improving the barrier performance of the coating and significantly enhancing the protective ability.
[0024] 2. Test results show that the assembled magnetic diatomite microcapsule anticorrosive filler is arranged in parallel in the coating, which increases the barrier area of the coating. When the corrosive medium invades the coating, the diatomite microcapsule corrosion inhibitor can quickly release the corrosion inhibitor and form a dense passivation film on the surface of the steel substrate, further delaying metal corrosion. The filler of this application overcomes the shortcomings of traditional fillers such as disordered dispersion, poor barrier effect, poor filler functionality, and short protection time. The method of magnetization modification and design of microcapsules and nanoparticle arrangement states has important reference value, and the prepared magnetic diatomite microcapsule corrosion inhibitor also has great application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 The magnetic diatomite microcapsule corrosion inhibitor filler Fe3O 4 / XRD and FTIR patterns of Ni-Co / DE@SP.
[0026] Figure 2 Thermal decomposition images of raw materials and magnetic Fe3O4 / Ni-Co / DE@SP anti-corrosion filler.
[0027] Figure 3 This is the SEM image of the Fe3O4 / Ni-Co / DE@SP material obtained in Example 1.
[0028] Figure 4 The SEM images of the coating with fillers added before and after magnetization on the surface of the steel substrate.
[0029] Figure 5 From bottom to top, they correspond to: Comparative Example 1, Comparative Example 2, Comparative Example 3, and the impedance modulus of the composite coating on the surface of the steel substrate in Example 1 after 90 days of 3.5% salt water testing.
[0030] Figure 6 The Fe3O4 nanoparticles prepared in Comparative Example 3 are spherical particles with a particle size of 50 to 100 nanometers.
[0031] Figure 7 SEM images of the coating with fillers added before and after magnetization on the surface of nickel-cobalt alloy.
[0032] Figure 8The electrochemical impedance spectra in correspond to: Comparative Example 1, Comparative Example 2, Comparative Example 3, and the impedance modulus of the nickel-cobalt alloy surface coating sample after 90 days of 3.5% salt water testing in Example 2. DETAILED DESCRIPTION
[0033] The present invention is described below in conjunction with specific examples, but the embodiments of the present invention are not limited thereto. Experimental methods without specific conditions in the examples are usually carried out according to conventional conditions and conditions described in the manual, or according to the conditions recommended by the manufacturer. The general equipment, materials, reagents, etc. used can be obtained from commercial channels unless otherwise specified. The raw materials required in the following examples and comparative examples are all commercially available.
[0034] Example 1
[0035] The preparation method of the magnetic diatomite microcapsule corrosion-inhibiting filler is as follows:
[0036] (1) Add 200 mg of diatomaceous earth to 60 g of deionized water and stir ultrasonically for 3 min to make it evenly dispersed;
[0037] (2) Then, nickel nitrate, cobalt nitrate, urea and ammonium fluoride were added to the diatomaceous earth suspension in step (1), and the mixture was stirred for 10 min. 2+ and Co 2+ The total molar amount is 1mmol, Ni 2+ / Co 2+ The molar ratio is 4:1. Urea and ammonium fluoride are 10 and 8 mmol, respectively. Then, a polytetrafluoroethylene-lined stainless steel autoclave is used to react at 80°C for 14 hours. After the reaction is cooled to room temperature, it is centrifugally washed three to four times with deionized water and alcohol. The obtained mixture is dried at 60°C for 4 hours to obtain double metal hydroxide-modified diatomaceous earth microcapsules, which are recorded as Ni-Co / DE;
[0038] (3) Prepare 3 g of sodium phosphate aqueous solution with a mass fraction of 15%. Add 0.5 g of the diatomite microcapsule intermediate obtained in step (2) to 3 g of sodium phosphate aqueous solution, and transfer the mixture to a vacuum drying oven at 60°C until it is completely dried to obtain double metal hydroxide-modified diatomite microcapsules loaded with corrosion inhibitors, which are recorded as Ni-Co / DE@SP. The pressure of the vacuum drying oven is -0.06 MPa (relative pressure).
[0039] (4) 2.58 g of sodium acetate, 0.43 g of ferric chloride and 21.5 g of ethylene glycol were mixed and stirred for 30 min to form a uniform solution. Then 0.43 g of the product obtained in step (3) was dispersed in the above ethylene glycol solution and reacted in an oven at 180° C. for 12 h to obtain a magnetic diatomite microcapsule corrosion-inhibiting filler having magnetic properties, corrosion inhibition and Cl-curing capabilities, which was recorded as
[0040] Fe3O 4 / Ni-Co / DE@SP.
[0041] The coating preparation method is as follows:
[0042] (1) 1.5 g of an oil-soluble epoxy resin and 1.0 g of an amine curing agent were dissolved in 10 g of ethyl acetate to obtain a resin-ethyl acetate solution.
[0043] 0.125 g of the magnetic diatomaceous earth microcapsule corrosion-inhibiting filler obtained above and 2.5 g of the resin-ethyl acetate solution were mixed and sprayed evenly on the surface of the steel substrate at 90° C. After spraying, the substrate was placed in an oven at 120° C. and kept for 4 hours to obtain an anti-corrosion coating.
[0044] Example 2
[0045] (1) Disperse diatomaceous earth in deionized water in the same manner as in Example 1 and disperse thoroughly.
[0046] (2) Then, nickel nitrate, cobalt nitrate, urea and ammonium fluoride were added to the diatomaceous earth suspension in step (1), and the mixture was stirred for 10 min. 2+ and Co 2+ The total molar concentration is 1mmol, Ni 2+ / Co 2+ The molar ratio is 2:1. Urea and ammonium fluoride are 20 and 12 mmol, respectively. Then, a polytetrafluoroethylene-lined stainless steel autoclave is used to react at 140°C for 8 hours. After the reaction is cooled to room temperature, it is centrifugally washed three to four times with deionized water and alcohol. The obtained mixture is dried at 80°C for 4 hours to obtain double metal hydroxide-modified diatomaceous earth microcapsules, which are recorded as Ni-Co / DE;
[0047] (3) Prepare 3 g of a 20% sodium phosphate aqueous solution. Add 1 g of the diatomaceous earth microcapsule intermediate obtained in step (2) to 3 g of the sodium phosphate aqueous solution, and transfer the mixture to a vacuum drying oven at 80°C until it is completely dried to obtain a double metal hydroxide-modified diatomaceous earth microcapsule loaded with a corrosion inhibitor, which is recorded as Ni-Co / DE@SP. The pressure of the vacuum drying oven is -0.06 MPa (relative pressure).
[0048] (4) 4.3 g of sodium acetate, 0.43 g of ferric chloride and 32.25 g of ethylene glycol were mixed and stirred for 30 min to form a uniform solution. Then 0.86 g of the product obtained in step (3) was dispersed in the above ethylene glycol solution and reacted in an oven at 200° C. for 12 h to obtain a magnetic, corrosion-inhibiting and Cl- - The magnetic diatomite microcapsule corrosion inhibition filler with solidification ability is recorded as Fe3O4 / Ni-Co / DE@SP.
[0049] The preparation method of the coating is exactly the same as that of Example 1, and the metal substrate is made of nickel-cobalt alloy.
[0050] (5) 1.5 g of an oil-soluble epoxy resin and 1.0 g of an amine curing agent were dissolved in 10 g of ethyl acetate to obtain a resin-ethyl acetate solution.
[0051] (6) 0.125 g of the magnetic diatomaceous earth microcapsule corrosion-inhibiting filler obtained above and 2.5 g of the resin-ethyl acetate solution were mixed and uniformly sprayed on the surface of the nickel-cobalt alloy substrate at 90° C. After spraying, the substrate was placed in an oven at 120° C. and kept for 4 hours to obtain an anti-corrosion coating.
[0052] Comparative Example 1
[0053] A pure epoxy coating was prepared according to the method for preparing the coating in Example 1, and was marked as EP:
[0054] 1.5 g of an oil-soluble epoxy resin and 1.0 g of an amine curing agent were dissolved in 10 g of ethyl acetate to obtain a resin-ethyl acetate solution.
[0055] The above 2.5 g of resin-ethyl acetate solution was sprayed uniformly on the steel substrate and the nickel-cobalt alloy surface at 90° C. After spraying, the substrate was placed in an oven at 120° C. and kept for 4 hours to prepare a pure epoxy coating without filler.
[0056] Comparative Example 2
[0057] Preparation of composite coating with Ni-Co / DE@SP filler:
[0058] (1) According to steps (1) and (2) of Example 1, Ni-Co LDH-modified diatom microcapsule filler Ni-Co / DE was obtained.
[0059] Prepare 3g of sodium phosphate aqueous solution with a mass fraction of 15%, add 0.5g of diatom microcapsule filler Ni-Co / DE obtained in step (2) to the sodium phosphate aqueous solution, and transfer the mixture to a vacuum drying oven at 80°C until it is completely dried to obtain double metal hydroxide-modified diatomite microcapsules loaded with corrosion inhibitors, recorded as Ni-Co / DE@SP. The pressure of the vacuum drying oven is -0.06MPa (relative pressure)
[0060] The composite coating with Ni-Co / DE@SP filler was prepared according to the method for preparing the coating in Example 1. The specific method is as follows:
[0061] 1.5 g of an oil-soluble epoxy resin and 1.0 g of an amine curing agent were dissolved in 10 g of ethyl acetate to obtain a resin-ethyl acetate solution.
[0062] 0.125 g of the above obtained double metal hydroxide modified diatomaceous earth microcapsules loaded with corrosion inhibitors and 2.5 g of the above resin-ethyl acetate solution were mixed and sprayed uniformly on the steel substrate and the surface of the nickel-cobalt alloy at 90° C. After spraying, the substrate was placed in an oven at 120° C. and kept for 4 hours to obtain an anti-corrosion coating.
[0063] Comparative Example 3
[0064] Composite filler physically mixed with Fe3O4 and double metal hydroxide modified diatomite microcapsules loaded with corrosion inhibitors:
[0065] (1) The method of Example 1 was used to prepare double metal hydroxide-modified diatomite microcapsules loaded with corrosion inhibitor.
[0066] (2) Preparation of Fe3O4 magnetic nanoparticles:
[0067] 2.58 g of sodium acetate, 0.43 g of ferric chloride and 21.5 g of ethylene glycol were mixed and stirred for 30 min to form a uniform solution, and then the solution was reacted in an oven at 180° C. for 12 h to obtain Fe3O4 magnetic nanoparticles.
[0068] (3) The Fe3O4 magnetic nanoparticles are blended with the double metal hydroxide-modified diatomaceous earth microcapsules loaded with corrosion inhibitors in step (1) to prepare a composite filler of Fe3O4 and the double metal hydroxide-modified diatomaceous earth microcapsules loaded with corrosion inhibitors.
[0069] Then, the composite coating was prepared on the steel substrate and the nickel-cobalt alloy surface respectively under the same conditions as in Example 1.
[0070] Figure 1 The magnetic diatomite microcapsule corrosion inhibitor filler Fe3O 4 / XRD and FTIR patterns of Ni-Co / DE@SP. DE refers to diatomite, SP refers to corrosion inhibitor sodium phosphate, and Ni-Co LDH refers to nickel-cobalt double hydroxide. Figure 1 It can be seen that magnetic Fe3O4, sodium phosphate and double hydroxide (LDH) were successfully loaded on diatomaceous earth, proving the successful synthesis of the material.
[0071] Figure 2 Thermal decomposition images of raw materials and magnetic Fe3O4 / Ni-Co / DE@SP anticorrosive filler. Ni-Co LDH, Fe3O4, SP (sodium phosphate) are pure substances that make up Fe3O4 / Ni-Co / DE@SP, Ni-Co / DE and Fe3O4 / Ni-Co / DE are intermediates that appear in the process of synthesizing fillers. The content of each component in the filler can be calculated through the decomposition rate of each pure substance.
[0072] Figure 2 Visible: Fe3O 4、 Diatomaceous earth and Ni-Co LDH have excellent thermal stability. SP begins to decompose at 60°C and loses some free water, but it does not affect the anti-corrosion effect. Therefore, the filler meets the requirements for use in marine heavy-duty anti-corrosion. The proportion and content of each pure substance component in the filler are calculated in Table 1.
[0073] Table 1 Decomposition rate and content data of each pure substance and filler
[0074]
[0075] Figure 3 This is the SEM image of the Fe3O4 / Ni-Co / DE@SP material obtained in Example 1. Figure 3 The morphology and structure of the composite material are shown as follows: (a) diatomite, (b) diatomite modified by Ni-Co LDH and sodium phosphate (SP), namely Ni-Co / DE@SP, and (c) Fe3O4 / Ni-Co / DE@SP. Figure 3 It can be observed that there are a large number of micropores on the surface of diatomite. After Ni-Co LDH modification and magnetization, it can be observed that the surface of diatomite is covered by a large number of lamellar LDHs, the pores disappear, and a large number of ferroferric oxide nanoparticles grow on the surface, which proves that the Fe3O4 / Ni-Co / DE@SP magnetic anti-corrosion filler has been successfully synthesized.
[0076] Figure 4 The SEM images of the coating with fillers added before and after magnetization on the surface of the steel substrate.
[0077] Among them, (a) comparative example 1 is a pure epoxy coating without adding filler, (b) comparative example 2 is a composite coating with Ni-Co / DE@SP filler added, and (c) example 1 is a composite coating with magnetic Fe3O4 / Ni-Co / DE@SP filler added.
[0078] Figure 4 It can be seen that: in (b), there are a lot of non-parallel arrangements of fillers, such as inclined or vertical arrangements with the steel plate substrate. In (c), the fillers can be arranged parallel to the steel plate in the coating, which proves that magnetizing the fillers can facilitate their parallel arrangement with the steel plate in the coating. In (c), it can be seen that the size of the magnetic Fe3O4 / Ni-Co / DE@SP fillers is 10-25μm.
[0079] Figure 5 From bottom to top, they correspond to: Comparative Example 1, Comparative Example 2, Comparative Example 3, and the impedance modulus of the composite coating on the surface of the steel substrate in Example 1 after 90 days of 3.5% salt water testing.
[0080] Figure 5It can be seen that after 90 days of testing, the impedance modulus of the pure epoxy coating (EP) of Comparative Example 1 is 6.01×10 7 Ω·cm 2 The impedance modulus of the composite coating prepared by Ni-Co / DE@SP without magnetization modification in comparative example 2 is 1.5×10 9 Ω·cm 2 The impedance modulus of the composite coating prepared by physical blending of Ni-Co / DE@SP and Fe3O4 in comparative example 3 is 2.4×10 9 Ω·cm 2 The impedance modulus of Fe3O4 / Ni-Co / DE@SP obtained by Fe3O4 modification in Example 1 is 7.83×10 9 Ω·cm 2 Since the impedance modulus can reflect the barrier capacity of the coating, this proves that the barrier capacity of Example 1 with the addition of magnetic oriented diatomaceous earth microcapsule filler is much higher than that of the pure epoxy coating (EP) without filler added in Comparative Example 1, the composite coating without magnetic modified filler in Comparative Example 2, and also much higher than that of the composite coating prepared by physical blending of Ni-Co / DE@SP and Fe3O4 in Comparative Example 3.
[0081] Figure 6 The Fe3O4 nanoparticles prepared in Comparative Example 3 are spherical particles with a particle size of 50 to 100 nanometers.
[0082] Figure 7 The SEM images of coatings with fillers added before and after magnetization on the surface of nickel-cobalt alloy; among them, (a) comparative example 1 is a pure epoxy coating without added fillers, (b) comparative example 2 is a composite coating with added Ni-Co / DE@SP fillers, and (c) example 2 is a composite coating with added magnetic Fe3O4 / Ni-Co / DE@SP fillers.
[0083] Figure 7 In the coating samples on the surface of nickel-cobalt alloy, it can be observed that: (b) there are a large number of randomly distributed fillers, such as inclined or vertical arrangement with the steel substrate. (c) The fillers can be arranged parallel to the steel plate in the coating, which proves that magnetization of the fillers can facilitate their parallel arrangement with the steel plate in the coating. (c) The size of the magnetic Fe3O4 / Ni-Co / DE@SP fillers can be seen to be 10-25μm. Whether on the surface of the steel substrate or the surface of the nickel-cobalt alloy, Fe3O4 / Ni-Co / DE@SP exhibits excellent orientation characteristics.
[0084] Figure 8 The electrochemical impedance spectra in correspond to: Comparative Example 1, Comparative Example 2, Comparative Example 3, and the impedance modulus of the nickel-cobalt alloy surface coating sample after 90 days of 3.5% salt water testing in Example 2.
[0085] Figure 8 It can be seen that after 90 days of testing, the impedance modulus of the pure epoxy coating (EP) of Comparative Example 1 is 1.23×10 7 Ω·cm 2 The impedance modulus of the composite coating prepared by Ni-Co / DE@SP without magnetization modification in Comparative Example 2 is 1.25×10 8 Ω·cm 2 The impedance modulus of the composite coating prepared by physical blending of Ni-Co / DE@SP and Fe3O4 in comparative example 3 is 4.25×10 8 Ω·cm 2 The impedance modulus of Fe3O4 / Ni-Co / DE@SP obtained by Fe3O4 modification in Example 2 is 9.1×10 8 Ω·cm 2 Since the impedance modulus can reflect the barrier capacity of the coating, this proves that the barrier capacity of Example 1 with the addition of magnetic oriented diatomaceous earth microcapsule filler is much higher than that of the pure epoxy coating (EP) without filler added in Comparative Example 1 and the composite coating without magnetic modified filler in Comparative Example 2, and is also much higher than that of the composite coating prepared by physical blending of Ni-Co / DE@SP and Fe3O4 in Comparative Example 3.
Claims
1. A magnetic diatomite microcapsule corrosion inhibition filler, characterized in that: The magnetic diatomite microcapsule corrosion inhibition filler is a diatomite microcapsule modified by a double metal hydroxide loaded with a corrosion inhibitor, and the diatomite microcapsule is loaded with magnetic nanoparticles; The magnetic nanoparticles are Fe3O4 magnetic nanoparticles.
2. The magnetic diatomite microcapsule corrosion-inhibiting filler according to claim 1, characterized in that: The magnetic diatomite microcapsule corrosion-inhibiting filler is disc-shaped and has a particle size of 10 to 25 μm.
3. A method for preparing the magnetic diatomite microcapsule corrosion-inhibiting filler according to claim 1, characterized in that: The preparation method comprises the following steps: A mixed solution of sodium acetate, trivalent iron salt and ethylene glycol is prepared, and diatomaceous earth microcapsules modified with double metal hydroxide loaded with corrosion inhibitor are dispersed in the mixed solution, and reacted at 180-200° C. for 12 hours to obtain magnetic diatomaceous earth microcapsule corrosion inhibition filler; Among them, the mass fraction of sodium acetate in the mixed solution is 20-30wt%, the ratio of the added amount of trivalent iron salt to sodium acetate is 1:(6-10), the mass ratio of the added amount of double metal hydroxide modified diatomaceous earth microcapsules loaded with corrosion inhibitor to the trivalent iron salt is (1-2):1, and the mass ratio of the amount of ethylene glycol to the trivalent iron salt is (50-75):
1.
4. The preparation method according to claim 3, characterized in that: The preparation method of the double metal hydroxide-modified diatomite microcapsules loaded with corrosion inhibitor is as follows: (1) Preparation of double metal hydroxide modified diatomite microcapsules: Dispersing diatomaceous earth in water to prepare a diatomaceous earth dispersion containing 0.1 to 0.2 g of diatomaceous earth per 100 g of water, adding a water-soluble nickel salt, a water-soluble cobalt salt, urea and ammonium fluoride to the dispersion, and then reacting at 80 to 140° C. for 8 to 14 hours, and cooling the reaction to room temperature to obtain a solid that is a double metal hydroxide-modified diatomaceous earth microcapsule; Among them, Ni 2+ / Co 2+ The molar ratio of is 4 to 2, the total molar ratio of metal cation to urea and ammonium fluoride is: 1: (10 to 20): 8 to 12; the molar mass ratio of metal cation to water is 1 mmol: 60 g; (2) Loading corrosion inhibitor sodium phosphate: The double metal hydroxide modified diatomite microcapsules obtained in step (1) are mixed with a sodium phosphate aqueous solution, wherein the mass fraction of sodium phosphate in the sodium phosphate aqueous solution is 15-20wt%, 0.5-1g of the double metal hydroxide modified diatomite microcapsules are mixed with 3g of the sodium phosphate solution, and then the mixture is transferred to a vacuum drying oven at 60-80°C until it is completely dried to obtain double metal hydroxide modified diatomite microcapsules loaded with corrosion inhibitor.
5. The magnetic diatomite microcapsule corrosion-inhibiting filler according to claim 1 is used for being arranged in parallel with a magnetic substrate in a coating and for corrosion protection.
6. The use according to claim 5, characterized in that The magnetic substrate is selected from a steel substrate or a nickel-cobalt alloy substrate.
Citation Information
Patent Citations
Preparation method of magnetic diatomite
CN104826601A
Preparation method of magnetic self-repairing microcapsules
CN105289435A
Preparation method of porous magnetic composite adsorbent and application of porous magnetic composite adsorbent in adsorbing dimethylarsonic acid
CN114700058A
Preparation method of composite coating for directionally arranging magnetic filler in coating under action of electromagnetic field
CN118667411A
Anticorrosive composite coating and preparation method thereof
CN118772725A
